Pengembangan dan Pelaksanaan Kurikulum Pendidikan Agama Pada SMA di Bawah Yayasan Keagamaan - Wahab Wahab (Analisa: Journal of Social Science and Religion, 2011)
The purpose of this study is to investigate the development and the implementationof  religious education curriculum developed by senior high schools  (SMA) under religious foundations. This is a case study of SMA Muhammadiyah I Palangkaraya. Research design applied in this study is Stufflebeam’s  CIPP (Context, Input, Process, Product). The results how:1) SMA Muhammadiyah I Palangkaraya develops not only curriculum designed by Ministry  of National Education but also local religious education one (curriculum developed by the foundation of Muhammadiyah); the way the school develops  the curriculum can also be considered as especial because it provides its nonmuslims  students facilities for learning their religious teachings, 2) some supporting factors are the participation of the foundation, the principal, and the school committee in the curriculum implementation, and 3) the obstacle of the curriculum implementation is the absence of a particular place such as laboratory for religious education.